EXTH-93. THE IRAK-4 INHIBITOR EMAVUSERTIB (CA-4948) FOR THE TREATMENT OF PRIMARY CNS LYMPHOMA. (14th November 2022) - von Roemeling, Christina; Doonan, Bently; Klippel, Kelena; Hoang-Minh, Lan; Ogando-Rivas, Elizabeth; Martinez, Elizabeth; Castillo, Paul; Iqbal, Madiha; Tun, Han; von Roemeling, Reinhard; Mitchell, Duane
Abstract: BACKGROUND: PCNSL is an aggressive brain tumor accounting for 3% of all CNS malignancies and is associated with poor prognosis. Standard of care treatment includes induction with high-dose methotrexate based chemoimmunotherapy followed by consolidation with autologous stem cell transplant or whole brain radiation. However, more than half of PCNSL patients cannot tolerate this intensive therapeutic intervention. Novel treatments are urgently needed. Toll-like receptor signaling pathway via MyD88/IRAK-4 signalosome is constitutively active in PCNSL secondary to MYD88 L265P mutation and represents an excellent therapeutic target. Emavusertib (CA-4948) is an oral first-in-class small molecule inhibitor of IRAK-4 that demonstrates clinical activity in patients with systemic Non-Hodgkin's Lymphoma, however it has not been evaluated in the CNS space. HYPOTHESIS: Emavusertib has anti-tumor activity against preclinical PCNSL. METHODS: Using multiparameter immunohistochemistry (IHC) and proteomics analysis, IRAK-1, IRAK-4, and NF-κB pathway activation were examined in patient PCNSL tissues as compared to normal controls. Plasma, cerebrospinal fluid, and brain tissue were assessed via UPLC-MS/MS for emavusertib drug concentration following single oral high dose in a murine model. Survival responses in preclinical PCNSL models were measured in response emavusertib treatment, along with in vivo tumor proliferation and downstream biomarker expression by multi-parameter IHC. RESULTS: Our data confirm elevated IRAK-1, IRAK-4, and NF-κB signaling in patient PCNSL. We show that emavusertib can achieve therapeutically relevant concentrations in the brain and CSF. Emavusertib impairs tumor cell proliferation in vitro and in vivo, and shows dose-dependent single-agent activity in preclinical PCNSL models. We confirm decreased ERK1/2, MAPK and NF-κB activation, indicative of downstream IRAK-4 inhibition. CONCLUSIONS: Our data supports that emavusertib demonstrates anti-tumor activity in the CNS space, warranting further preclinical and clinical evaluation of this agent for the treatment of PCNSL.